2009
DOI: 10.4334/jkci.2009.21.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Reinforced Recycled Aggregate Concrete Beams

Abstract: These days the amount of demolished concrete waste has been increasing due to reconstruction and redevelopment of aged buildings. So the use of recycled aggregates is recommended to solve environmental problems. Some investigations have been carried out to study the flexural behavior of reinforced concrete beams with recycled aggregates. But these have some limitation due to the use of low quality recycled aggregates and small-scale specimens in the laboratory. The purpose of this experimental study is to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…They reported an increase in the deflections as the amount of RCA is increased. Similar results were reported by Song et al [19] However, they also reported that the addition of RCA into concrete has little effect on the ultimate moment capacity and the flexural crack width of the tested specimens.…”
Section: Introductionsupporting
confidence: 90%
“…They reported an increase in the deflections as the amount of RCA is increased. Similar results were reported by Song et al [19] However, they also reported that the addition of RCA into concrete has little effect on the ultimate moment capacity and the flexural crack width of the tested specimens.…”
Section: Introductionsupporting
confidence: 90%
“…The first step in this research was the collection of all available studies on shear and flexural strength of RAC beams. A review of existing literature yielded 16 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] carried out in the period from 2001 to 2015 with a total of 217 experimental results. All of the studies were comparative tests of RAC and NAC beams.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…(11), section 6.2.3 of EC2. Contrary to MC2010, for predictions according to EC2 the angle θ wasn't calculated but rather it was measured from the photos given in studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] as the inclination of the critical crack at beam mid-depth. However, its value was restricted to the interval 21.8º-45º as given in the same section.…”
Section: Shear Strength Of Slender Beams With Stirrupsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the advanced development of technology, recent waste management may result in recycled aggregate with MATEC Web of Conferences 195, 01017 (2018) https://doi.org/10.1051/matecconf/201819501017 ICRMCE 2018 quality equal to the natural aggregate (NA). Thus, the potential of RCA as a structural element and for high added-value utilization has been rapidly growing [4].…”
Section: Introductionmentioning
confidence: 99%